Yersinia pseudotuberculosis BarA-UvrY Two-Component Regulatory System Represses Biofilms via CsrB - Schachterle, Jeffrey K.; Stewart, Ryan M.; Schachterle, M. Brett; Calder, Joshua T.; Kang, Huan; Prince, John T.; Erickson, David L. (Frontiers in Cellular and Infection Microbiology, 2018)
The formation of biofilms by Yersinia pseudotuberculosis (Yptb) and Y. pestis requires the hmsHFRS genes, which direct production of a polysaccharide extracellular matrix (Hms-ECM). Despite possessing identical hmsHFRS sequences, Yptb produces much less Hms-ECM than Y. pestis. The regulatory influences that control Yptb Hms-ECM production and biofilm formation are not fully understood. In this study, negative regulators of biofilm production in Yptb were identified. Inactivation of the BarA/UvrY two-component system or the CsrB regulatory RNA increased binding of Congo Red dye, which correlates with extracellular polysaccharide production. These mutants also produced biofilms that were substantially more cohesive than the wild type strain. Disruption of uvrY was not sufficient for Yptb to cause proventricular blockage during infection of Xenopsylla cheopis fleas. However, this strain was less acutely toxic towards fleas than wild type Yptb. Flow cytometry measurements of lectin binding indicated that Yptb BarA/UvrY/CsrB mutants may produce higher levels of other carbohydrates in addition to poly-GlcNAc Hms-ECM. In an effort to characterize the relevant downstream targets of the BarA/UvrY system, we conducted proteomic analysis to identify proteins with lower abundance in the csrB::Tn5 mutant strain. Urease subunit proteins were less abundant and urease enzymatic activity was lower, which likely reduced toxicity towards fleas. Loss of CsrB impacted expression of several potential regulatory proteins that may influence biofilms, including the RcsB regulator. Overexpression of CsrB did not alter the Congo-red binding phenotype of an rcsB::Tn5 mutant, suggesting that the effect of CsrB on biofilms may require RcsB. These results underscore the regulatory and compositional differences between Yptb and Y. pestis biofilms. By activating CsrB expression, the Yptb BarA/UvrY two-component system has pleiotropic effects that impact biofilm production and stability.